Lipoxin A4 Restores Septic Renal Function via Blocking Crosstalk Between Inflammation and Premature Senescence - Chen, Chaojin; Qiu, Rongzong; Yang, Jing; Zhang, Qian; Sun, Guoliang; Gao, Xiaofeng; Hei, Ziqing; Ji, Haocong (Frontiers in Immunology, 2021)
Acute kidney injury (AKI) occurs in half of patients with septic shock, resulting in unacceptably high mortality. However, effective preventive treatments are still lacking. We hypothesized that pretreatment with lipoxin A4 (LXA4), known to promote inflammation resolution, may attenuate septic AKI via blocking crosstalk between inflammation and cellular senescence. In this study, rats developed AKI following cecal ligation and puncture (CLP), as evidenced by a dynamic increase in serum creatinine, blood urea nitrogen, urinary kidney injury molecule-1, neutrophil gelatinase-associated lipocalin, and pathological injury, accompanied by increased levels of inflammation (IL-6, TNF-α, and HMGB1) and tubular cell senescence. While, on the one hand, inhibition of senescence with rapamycin restored renal function and attenuated septic inflammatory response, on the other hand, LXA4 administration inhibited renal inflammation and tubular epithelial cell senescence after CLP. Ultimately, pretreatment with LXA4 significantly restored renal function and increased the survival rate of rats after CLP. Furthermore, LXA4 inhibited NF-κB-mediated inflammatory response and the p53/p21 senescence pathway in vivo and in vitro. However, the effect was reversed by PPAR-γ siRNA and antagonist. These results indicated that LXA4 exerted its renoprotective effects by blocking the crosstalk between inflammation and premature senescence in a PPAR-γ-dependent manner. Our findings also suggested that premature senescence plays a critical role in septic AKI and that inhibition of the crosstalk between inflammation and premature senescence may represent a new and major mechanism through which LXA4 attenuates septic AKI.